ANALYSIS OF SUCCESS FACTOR SISTEM INFORMASI AKADEMIK (SIAKAD) USE THE DELONE AND MCLEAN MODEL (CASE STUDY STIE MUHAMMADIYAH PRINGSEWU LAMPUNG) - Roby Novianto (Jurnal TAM (Technology Acceptance Model), 2020)
The purpose of this research is to analize factors that influance the successful implementation of Sistem Informasi Akademik (SIAKAD) at STIE Muhammadiyah Pringsewu Lampung. This research use the information system success model of Delon McLean wich modified into STIE Muhammadiyah Pringsewu Lampung needed. The data analisys base on Structural Equation Modeling (SEM) with Analysis of Moment Structures (AMOS) as tools. The result of this research show that 4 of 5 hypotheses are significanly accepted which information quality give positive influential to user satisfaction, system quality give positive influential to user satisfaction, service quality give positive influential to user satisfaction and user satisfaction give positive influential to net benefits. Success factors generated from this research will be used as recommendations for the next development of SIAKAD so service quality of SIAKAD to STIE Muhammadiyah Pringsewu Lampung civitas akademica will improved.